(untitled) (Bangladesh Journal of Medical Physics, 2013)
A simple electrical gastrometer has been innovated and developed based on short circuit current produced by a voltaic cell comprising of two dissimilar metallic electrodes in a probe on which a specific volume of saliva is placed. This has been used to take data from 388 normal subjects and 622 subjects with gastric acidity problems to various degrees, assessed by the author in his capacity as a village doctor. A grading scheme was also developed to categorise the condition of the disorder based on the intensity of discomfort. A good correlation has been observed between the assessed degree of gastric acidity and the currents produced in this gastrometer. Thus this low cost device may be useful in diagnosing gastric problems. Furthermore, treatment given to these patients based on this estimation also produced relief in majority of cases. DOI: http://dx.doi.org/10.3329/bjmp.v4i1.14705 Bangladesh Journal of Medical Physics Vol.4 No.1 2011 149-151